Effects of defatted black soldier fly larvae (dbsfl) on the blood parameter, carcass quality and cost analysis of crossbreed village chicken - Muhammad Ameer Rustam Alias (2026)
An abstract of the research paper presented to the Faculty of Veterinary Medicine, Universiti Malaysia Kelantan, in partial requirement of the course DVT 55204 – Research Project. This study evaluated the effects of Defatted Black Soldier Fly Larvae (DBSFL) on the blood parameters, carcass quality and cost analysis for rearing the crossbreed village chicken. Three different dietary treatments were tested which are T1 (100% commercial feed), T2 (95% commercial feed + 5% DBSFL) and T3 (90% commercial feed + 10% DBSFL). The hematological and biochemical parameters were not significantly affected (p >0.05), indicate that the inclusion of DBSFL at low level is safe to be consumed by the chicken. Only total protein showed a significant increase in T3 (p = 0.01). In carcass quality, most parameters were not significantly different (p > 0.05), except for wing weight (p =0.01) which was recorded as the lowest for T3. Growth performance showed similar body weight gain across treatments, although feed intake and feed conversion ratio differed significantly (p < 0.05). Cost analysis demonstrated that a 5% DBSFL in T2 produced the highest gross profit (RM18.61) and net profit (RM 6.64). To conclude, the inclusion of DBSFL up to 10 % did not result in the hematological, biochemical or carcass quality of the chicken. Therefore, a 5% inclusion of DBSFL is the most economically optimal dietary treatment with good carcass quality and profit in rearing crossbreed village chicken.